The Effect Of Service Quality And Trust On Customer Satisfaction At Bank Bengkulu Girimulya Support Branch - M. Andres Saputra; Sulisti Afriani; Zahrah Indah Ferina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the effect of service quality and trust on customer satisfaction at Bank Bengkulu, Girimulya Sub-Branch. The sample in this study was 96 Tabunganku customers at Bank Bengkulu, Girimulya Sub-Branch. Data collection was carried out using a questionnaire and the analysis method by multiple linear regression, test of determination and hypothesis testing. The results of the regression analysis show Y = 11.647 + 0.320X1 + 0.425 X2, this illustrates a positive direction of regression, meaning that there is a positive influence between X1 (service quality) and X2 (trust) on customer satisfaction (Y). This means that if the variables of service quality and trust increase, it will increase customer satisfaction. The coefficient of determination is 0.416. This means that X1 (service quality) and X2 (trust) affect customer satisfaction (Y) by 41.6%, while the remaining 58.4% is influenced by other variables not examined in this study. The results of the t test at the 0.05 significance level explain that partially the variables of service quality and trust have a significant influence on the customer satisfaction variable of Bank Bengkulu, Girimulya Sub-Branch. The results of the F test at the 0.05 significance level explain that the variables of service quality and trust have a simultaneous (joint) influence on customer satisfaction at Bank Bengkulu, Girimulya Sub-Branch.